Analysis of Pulmonary and Hemodynamic Parameters for the Weaning Process by Using Fuzzy Logic Based Technology - Kilic, Ugur; Gulluoglu, Mehmet Tahir; Guler, Hasan; Kaya, Turgay (Springer-Verlag Berlin, 2016)
This study aims to achieve accurate weaning process which is very important for patient under mechanical ventilation. The developed weaning algorithm was designed on LabVIEW software and fuzzy system designer part of LabVIEW software was used during to develop that algorithm. The developed weaning algorithm has six input parameters which are maximum inspiratory pressure (MIP), tidal volume on spontaneous breathing (TVS), minute ventilation (VE), heart rate, respiration per minute (RPM) and body temperature. 20 clinical scenarios were generated by using Monte-Carlo simulations and Gaussian distribution method to evaluate performance of the developed algorithm. An expert clinician was involved to this process to evaluate the each generated clinic scenario to determine weaning probability for the each patient. Student t-test for p < 0.05 was used to show statistical difference between the developed algorithm and clinician's evaluation. According to student t-test, there is no statistical difference for 98.2 % probability between the developed algorithm and the clinician's evaluation of weaning probability.
22nd International Conference on Information and Software Technologies (ICIST) -- OCT 13-15, 2016 -- Druskininkai, LITHUANIA
Keywords: Mechanical ventilation; Weaning; Fuzzy system; Student t-test; Gaussion distribution; LabVIEW